Impact of New Shift Models for Doctors Working at a German University Hospital for Gynaecology and Obstetrics Four Years After Implementation. Can They Meet the European Working Time Directive Without Increasing Costs? - Maschmann, J.; Holderried, M.; Blumenstock, G.; Bamberg, M.; Rieger, M. A.; Wallwiener, D.; Brucker, S. (Geburtshilfe und Frauenheilkunde, 2013)
Background: The impact of the European Working Time Directive and subsequent collective wage agreements for doctors from 2006 onwards were substantial. So far, no systematic evaluation of their application in Germany has been performed. We evaluated the impact four years after implementation of new shift models in a University Hospital for Gynaecology and Obstetrics (UHGO). Methods: A new shift model was created together with doctors of Tübingen UHOG in 2007 and implemented in 2008. Documentation of working hours has hence been done electronically. Adherence to the average weekly working time limit (AWTL) and the maximum of 10 h daily working time (10 h-dwt) was evaluated, as well as staffing costs in relation to case-weight points gathered within the German DRG (diagnosis related groups) System. Results: Staff increased from a mean of 44.7 full time equivalent (FTE) doctors in 2007 to 52.5 FTE in 2009, 50.8 in 2010, and 54.5 in 2011. There was no statistically significant difference of the monthly staff expenditures per case-weight between the years 2009 or 2010 vs. 2007. 2011, however, was significantly more expensive than 2007 (p = 0.02). The internal control group (five other departments of the university hospital) did not show an increase during the same period. AWTL were respected by 90, 96, and 98 % in 2009, 2010, and 2011, respectively. Of all shifts 10 h-dwt was exceeded by 7.4 % in 2009, 1.3 % in 2010, and 2.6 % in 2011, with significant differences between 2009 and both, 2010 and 2011 (p < 0.001), and between 2010 and 2011 (p = 0.02). Discussion: AWTL and 10 h-dwt could be continuously respected quite well after implementation of the new shift model without increasing the cost/earnings ratio for the first two years. However, in 2011 the ratio increased significantly (p = 0.02).
Keywords: gynecology; EWTD; doctors; shift model; university hospital